2016
DOI: 10.1186/s12906-016-1117-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive use of essential oils following scaling and root planing –a randomized clinical trial

Abstract: BackgroundHitherto no study has been published on the effect of the adjunctive administration of essential oils following scaling and root planing (SRP). This study describes the effect of a mouthrinse consisting of essential oils (Cymbopogon flexuosus, Thymus zygis and Rosmarinus officinalis) following SRP by clinical and microbiological variables in patients with generalized moderate chronic periodontitis.MethodsForty-six patients (aged 40–65 years) with moderate chronic periodontitis were randomized in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…A recent study investigated whether the adjunctive use of a mouthwash containing three natural essential oils ( Cymbopogon flexuosus oil, Thymus Zygis oil, Rosmarinus officinalis ) following sub-gingival debridement and scaling and root planning (SRP) could improve the clinical results regarding changes of the clinical parameters of PD, CAL and bleeding on probing (BoP) (Azad et al, 2016). Significant improvements of AL, PD, and BoP occurred in both groups after 3 months ( p < 0.001); PD and BoP being significantly lower in the TG.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated whether the adjunctive use of a mouthwash containing three natural essential oils ( Cymbopogon flexuosus oil, Thymus Zygis oil, Rosmarinus officinalis ) following sub-gingival debridement and scaling and root planning (SRP) could improve the clinical results regarding changes of the clinical parameters of PD, CAL and bleeding on probing (BoP) (Azad et al, 2016). Significant improvements of AL, PD, and BoP occurred in both groups after 3 months ( p < 0.001); PD and BoP being significantly lower in the TG.…”
Section: Discussionmentioning
confidence: 99%
“…Mouthwash containing essential oil might also be more effective in killing dental bacteria. A randomized-controlled clinical trials involving patients with moderate chronic periodontitis indicated that combined using mouthwash with essential oil from Cymbopogon flexuosus , Thymus zygis and Rosmarinus officinalis had anti-biofilm potential in the subgingiva in patients with good tolerability [ 94 ]. As indicated in a randomized double-blind trail, mouthrinses consist of Lemongrass oil reduced oral malodour for 8-day treatment, which might due to its selectively anti-microbial effect against Aggregatibacter actinomycetemcomitans ATCC43718 and Porphyromonas gingivalis W50 [ 95 ].…”
Section: Natural Anti-biofilm Agents Under Clinical Evaluationmentioning
confidence: 99%
“…(rosemary), which is widely used in food, cosmetics, spices and flavoring in many countries. A number of authors have conducted clinical trials to assess the effectiveness of toothpastes containing herbs, as well as, there are reports in the scientific literature of researches with mouthwashes which contained the rosemary in its composition (5,(18)(19)(20). However, the present study is the first to perform clinical analysis on rosemary using oral health indices and a defined therapeutic dose of the plant extract.…”
Section: Discussionmentioning
confidence: 94%
“…Natural products are a valuable and unexplored source of potentially effective antimicrobials, with low levels of toxicity. Recent advances in analytical technology, particularly those related to phytotherapy, have created a new era of anti-plaque therapies and natural products (17,18). In this sense, plant extracts and their compounds appear as na alternative for the treatment of periodontal diseases in view of the fact that pharmacological research evoked the antibacterial and anti-inflammatory activities of rosemary.…”
Section: Discussionmentioning
confidence: 99%